AN OVERVIEW OF CONSTRAINTS TO SOYBEAN PRODUCTION IN THE NORTHERN REGION OF GHANA - A-R. S., Mohammed; Al-hassan, S.; Jatoe, J. B. D (UDS International Journal of Development, 2018)
This paper investigates the constraints that impede soybean production in the Northern Region of Ghana. The paper describes the trend in soybean production in the Northern Region from 2001 to 2010. It identifies and ranks the constraints to soybean production in the region. Ms Excel was used to plot soybean production figures from 2001 to 2010 sourced from SRID, MoFA. The Kendall’s coefficient of concordance (W) model was used to rank the identified constraints impeding soybean production. The results indicate that output of soybean increased from about 36,852MTs in 2007 to about 99,408MTs in 2010 in the study area (about 169.7%). Inadequate farm credit, inadequate rainfall and lack of improved planting materials are the most serious constraints hindering soybean production. The paper recommends that there should be timely delivery of credit in the right amount requested by soybean farmers by the Ministry of Food and Agriculture, SADA and other stakeholders. Quality planting materials should be made accessible and affordable to farmers by Agricultural stakeholders in Ghana. Keywords: Soybean, Production, Constraints, Trends, Northern Region